Influence of the polishing technique on the roughness and profile of bisacryl- based materials - Garrido, Lorena de Mello Alcântara (2017)
Statement of the problem. The choice of technique and material for making provisional restorations is important. The material must have enough strength to withstand the masticatory loads without suffering deformation or fracture and its surface must have good finishing and polishing to reduce biofilm accumulation. Objective. The aim of this study was to investigate what is the best polishing protocol for different bis-acryl materials with the intention to obtain a smooth surface. Materials and methods. A total of 104 samples were made (15mm long x 5mm wide x 4mm high) and were divided into three study factors: material (Protemp 4, Structur 3, Dencor, Z350XT), polishing (Sof-Lex Pop On and Sof-Lex Spiral discs) and period (initial, postpolishing, post-brushing). Thirteen samples were made per material group, and at each step, a sample was randomly taken for the purpose of submitting to scanning electron microscopy (SEM) analysis, totaling 24 samples to be submitted to this test, and thus, resulting in 80 samples to be brushed, and 10 samples per group for statistical analysis (n = 10). In all samples, surface roughness readings (m) were performed at all periods, that is, after they were made, after polishing and after brushing through the rugosimeter (Hommel tester). At the end, the 80 samples were read in a profilometer for analysis of surface wear. The results for the roughness were submitted to ANOVA for three criteria followed by the Tukey`s test ( = 0.05), and for the surface wear test, the results were submitted to ANOVA for two criteria followed by the Tukey`s test ( = 0.05). Results. Protemp 4 bis-acryl showed higher values of surface roughness when polished with Sof-Lex Spiral discs (0.284 m) when compared to Sof-Lex Pop On discs polishing (0.075 m). After brushing, there was an increase of surface roughness for both types of polishing. Sof-Lex Spiral discs (0.375 m) and Sof-Lex Pop On discs (0.359 m), but with no significant differences (p>0.05). For the surface wear results, there was no statistical difference between the groups: Protemp 4 bis-acryl resin with Sof-Lex Pop On polishing (13.95 m) and polishing with the Sof-Lex Spiral discs (14.91 m ) and the Z350XT composite resin group polished with the two polishing systems - Sof-Lex Pop On and Sof-Lex Spiral (12.61m, 12.70m, respectively). Structur 3 bis-acryl resin showed lower surface roughness results when polished with Sof-Lex Pop On discs (0.113 m) compared to Sof-Lex Spiral discs (0.223 m). For the surface wear results, there was no difference between the groups of the Structur 3 bis-acryl resin, but the values for both the polished group with Sof-Lex Pop On discs (15.77m) and the group polished with the Sof-Lex discs Spiral (15.40 m) were very close to the values of the group of the Protemp 4 bis-acryl resin and the Z350XT composite resin group, with statistical difference. The two tested bis-acryl resins, the Protemp 4 and Structur 3 in the two polishing systems, showed better surface roughness values (Ra) and lower surface wear values than the Dencor acrylic resin. Dencor acrylic resin group showed the highest values of surface roughness at all times. However, after polishing and brushing, the surface roughness presented lower values, when compared to Ra initial values, but this material showed the highest surface wear values (31.21 m).The resin composite group Z350XT which polishing procedure was Sof-Lex Pop On discs showed lower values (0.039 m). There were no statistically significant differences in surface roughness at all periods and the surface roughness increased after brushing, followed by lower values also for surface wear (12.61 m). Conclusion. By polishing it is possible to improve the surface roughness of the resinous materials, however, the technique, the operator, the materials to be polished and the finishing and polishing system are directly correlated. For the present study, the system that obtained the best results was the Sof-Lex Pop On discs, and the bis-acryl resin that presented the lowest Ra number was the Structur 3 bis-acryl resin. For surface wear, the Structur 3 bis-acryl resin showed higher values compared to the results of the Protemp 4 bis-acryl resin group, which, in turn, showed surface wear values close to that of the Z350 XT composite resin group.